Association between Pacifier Use, Bottle-Feeding, and Pre- Postnatal Variables: A Cohort Study - Letícia Santos Alves de Melo; Lorena Fonseca Silva; Silvio Rocha Corrêa da Silva; Fernanda Lopez Rosell; Aylton Valsecki Júnior; Angela Cristina Cilense Zuanon; Elaine Pereira da Silva Tagliaferro (Association of Support to Oral Health Research (APESB), 2023)
Objective: To determine the prevalence and analyze the variables associated with the use of pacifiers and/or bottles by infants up to 6 months of age. Material and Methods: Data on sociodemographic characteristics, intention to offer pacifier and bottle-feeding, pregnancy and breastfeeding (BF) variables were collected at baseline by interviews and a self-administered questionnaire among pregnant women in the 3rd trimester. After delivery, mother-baby binomials were followed by phone calls at the 1st, 3rd, and 6th months of the baby's life (n=467) to gather information on the type of delivery, baby's gender, BF in the first hour of the newborn's life, baby's weight, mother's return to work, and oral habits. Association analyses were performed using logistic regression models with a 5% significance level with the pacifier/bottle-feeding use as the outcome. Results: Most mothers (52.5%) reported their babies used bottle-feeding, 48.2% used pacifiers and 33.4% used both of them throughout the 6 months. Intention to offer pacifier and bottle-feeding was reported by 45.0% and 54.8% of the mothers at the 3rd trimester of the pregnancy, respectively. Not living in one's own residence (OR=1.53; 95%CI: 1.05-2.24) and having the prenatal intention of offering a pacifier (OR=2.50; 95%CI: 1.63-3.83) to the baby were significantly associated with pacifier use. Variables significantly associated with bottle-feeding were mother's return to work (OR=2.48; 95%CI: 1.54-3.97), baby's lower birth weight (OR=1.58; IC95%: 1.07-2.33), and prenatal intention to offer bottle-feeding (OR=2.51; 95%CI 1.56-4.04). Conclusion: About half of the babies used pacifiers or were bottle-fed, which were associated with the mother's prenatal intention to offer them to their babies and socioeconomic factors.